[P116] Transition of the patient dose by the diagnostic X-ray examinations in the area of the local-area survey by the novel patient dose calculation system. (August 2018) - Sato, Hitoshi; Erika, Nakajima
Abstract : Purpose: The diagnostic reference level (DRLs) was proposed to a patient dose as a tool for optimization by diagnostic X-ray examination. The purpose of this study was to estimate the entrance surface dose for the different types of X-ray examinations of the hospital. In this study, a novel calculation system was developed for estimating the entrance surface doses and the result of the local survey about the patient dose of the local area was reanalyzed. Methods: The entrance surface dose by novel calculation system (call estimation patient dose calculation system: EPD) is calculated using the parameter of an X-ray output (tube voltage, current time product, filtration, focus-skin distance, field size, etc.). The coefficient which standardized the output in each conditions based on the measurement result of a standard air kerma is used for this calculation system. Although the standard body thickness according to types of X-ray examination, exposure field size, etc. are used in initial setting, modification is also possible respectively. The entrance surface dose by means of survey continuously conducted by the Ibaraki Association of Radiologic Technologists from 1988 to the hospital in Ibaraki Prefecture was re-analyzed using this calculation system. Results: As for the calculation result, a maximum of +20% of difference was confirmed to the measurement result of an ionization chamber type dosimeter (DC300: Wellhofer). However, it is proper as an estimate to the survey for attaining rationalization of a dose. There is a limit in accurate dose estimate by the range of 40–150 kV tube voltage, the difference in filtration, etc. Although the dose was a decline tendency on the whole in the re-analysis result of the patient dose by the novel dose calculation system, transition is trifling in recent years. Conclusions: A novel calculation system was developed for estimating the entrance surface dose and the result of the local survey about the patient dose of the area was reanalyzed. The accuracy of dose estimation was investigated and the usefulness was confirmed. The transition of the level of the patient doses in a local area has been grasped.